2020
DOI: 10.1101/2020.08.10.20172197
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Simultaneous [11C]Raclopride Positron Emission Tomography and Functional Magnetic Resonance Imaging Investigation of Striatal Dopamine Binding in Autism

Abstract: Background: The social motivation hypothesis of autism suggests that autism spectrum disorder (ASD) is characterized by impaired motivation to seek out social experience early in life that interferes with the development of social functioning. This framework posits that impaired mesolimbic dopamine (DA) function underlies compromised responses to social rewards in ASD. Although this hypothesis is supported by functional magnetic resonance imaging (fMRI) studies, no molecular imaging study has evaluated striata… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 84 publications
(93 reference statements)
0
2
0
Order By: Relevance
“…At the same time, such studies could describe the effects of dopamine modulators on essential circuits, permitting individualized therapy for certain subsets of patients. A recent PET/functional magnetic resonance imaging study reported impaired striatal phasic dopamine release to incentives, providing support for the SMT of ASD [95]. However, Kubota et al [96] reported similar DRD1 binding capacity, while Schalbroeck et al [97] found no significant difference in striatal dopamine synthesis capacity between adults with ASD and neurotypical controls.…”
Section: Future Prospectsmentioning
confidence: 99%
“…At the same time, such studies could describe the effects of dopamine modulators on essential circuits, permitting individualized therapy for certain subsets of patients. A recent PET/functional magnetic resonance imaging study reported impaired striatal phasic dopamine release to incentives, providing support for the SMT of ASD [95]. However, Kubota et al [96] reported similar DRD1 binding capacity, while Schalbroeck et al [97] found no significant difference in striatal dopamine synthesis capacity between adults with ASD and neurotypical controls.…”
Section: Future Prospectsmentioning
confidence: 99%
“…In turn, PET imaging of radioligand binding to the dopamine active transporter (DAT) showed increased binding in the orbitofrontal cortex of highfunctioning adults with ASD (Nakamura et al, 2010); however, changes in dopaminergic function at rest have not been detected universally (Makkonen et al, 2008). During task performance, a reduction in phasic striatal DA events evoked by social stimuli in children and adolescents with ASD have been reported in several studies (Scott-Van Zeeland et al, 2010;Zürcher et al, 2020). Together, these data support the involvement of functional changes in dopaminergic signaling in ASD.…”
Section: Brain Imaging and Pharmacological Interventions In Individuals With Asdmentioning
confidence: 99%